Participatory organic research in the USA and Italy: Across a continuum of farmer–researcher partnerships. Issue 4 (28th July 2016) - Delate, Kathleen; Canali, Stefano; Turnbull, Robert; Tan, Rachel; Colombo, Luca
Abstract: Organic agriculture continues to expand in the USA and in the European Union (EU), particularly in Italy, which had 48, 650 organic farms in 2014 compared with 19, 474 in the USA. Additionally, EU support for organic research is nearly double than that of the USA. Along with increased support for organic research, the EU organic community has achieved recognition at the European Commission policy level for a dedicated innovation platform, advocating the practice of farmer-first models for participatory research. The US land-grant universities have a long history of on-farm research, primarily through the Extension Service, but the need exists for more inclusive, second-loop, co-research with organic farmers. A survey was conducted of organic farmers and researchers in Italy and in the USA to ascertain the extent of participatory organic research activities and experiences, and explore the vision each group had for the future of co-innovation between organic farmers and researchers. Results indicated that, despite the higher level of organic research support in the EU, the percentage of researchers involved in on-farm/participatory organic research was equivalent in Italy and the USA, presumably due to the more recent emphasis in Italian/EU agricultural research agendas on the importance of farmer knowledge and participation in organic research. Overall, 60% of surveyed organic researchers in both countries cited involvement in on-farm/participatory organic research, with 'farming systems' and 'nutrient/pest management' the main research focus in the USA, compared with 'farming systems' and 'equipment' in Italy. Both countries' researchers expressed their vision of participatory research as helping to improve communication between researchers and farmers, to enable work on relevant research, and to allow farmers to adapt technologies to their own conditions. Organic farmers in Italy completed survey questionnaires as part of a field day activity, leading to more Italian farmers responding to the survey, compared with USA counterparts who were queried via e-mail. Organic farmers in Italy identified 'knowledge-sharing' as a critical value of participatory research, and were conducting on-farm research with less compensation than US farmers. The 'lack of time' was cited as the most important constraint limiting participatory research by Italian and US farmers, although the 'lack of common language' also was rated as potentially impairing full participation. Lessons shared between EU and US organic researchers as a result of this project included methods to institute policies aimed at increasing support for organic research and co-innovations with organic farming communities, and connecting experienced on-farm researchers in the US with Italian colleagues to enhance collaborative activities with organic farmers.